PERAN KEPALA DAERAH DALAM MENYELENGGARAKAN PENDIDIKAN DASAR DI KOTA CIMAHI TAHUN 2023: The Role Of The Regional Head In Organizing Basic Education In Cimahi City In 2023 - Ficky Sarwafatta Afganisya; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2025)
The implementation of primary education in Cimahi City in 2023 raises issues related to the exercise of the Regional Head’s authority within the framework of regional autonomy. This is due to a gap between the policies stipulated in Regional Regulation of Cimahi City Number 8 of 2021 concerning the Implementation of Education and their practical implementation in the field. The research problems formulated in this study are: how does the Regional Head play a role in administering primary education in Cimahi City in 2023? and what obstacles are encountered in its implementation? This study employs a normative juridical method using statutory and case study approaches. The findings and conclusions show that Regional Regulation Number 8 of 2021 provides a clear and firm legal foundation for the administration of education. However, its implementation still faces several obstacles, such as limited budget allocation, shortage of teaching personnel, inadequate educational infrastructure, and weak cross-sectoral coordination